Efficacy and safety of catheter-directed thrombolytic therapy of alteplase and urokinase for the treatment of deep vein thrombosis: a Meta-analysis - Hong-Yan LI; Hai-Shan WANG; Yong-Bo WANG; Xiu-Qing SHI; Si-Yu YAN; Tao WANG (Yixue xinzhi zazhi)
Objective To systematically review the effectiveness and safety of cathe-ter-directed thrombolytic therapy (CDT) using alteplase and urokinase in the treatment of deep vein thrombosis (DVT) in the lower extremities.Method PubMed, The Cochrane Library, Web of Science, Embase, WanFang Data, CNKI and SinoMed databases were searched electronically to collect randomized clinical trials and cohort sudies on CDT using alteplase and urokinase in the treatment of DVT in the lower extremities from inception of the databases to December 2021. Two reviewers independently screened literature, extracted data, and assessed the risk of bias in included studies, a Meta-analysis was performed using RevMan 5.4 software.Result A total of 7 cohort studies involving 598 patients were included. The results of the Meta-analysis showed that there was no sta-tistically significant difference between alteplase and urokinase in the clinical effectiveness rate [RR=1.07, 95%CI(0.91, 1.25), P=0.43] and thrombolysis rate [RR=1.08, 95%CI(0.99, 1.16), P=0.07]; the thrombolytic time of alteplase was shorter than that of urokinase [MD=-1.12, 95%CI(-1.93, -0.31), P=0.007]; there were no statistically sig-nificant differences between alteplase and urokinase in the incidence of minor bleed-ing[RR=1.19，95%CI(0.70, 2.00), P=0.52] and major bleeding[RR=0.73, 95%CI(0.27, 1.98), P=0.54]. Conclusion The effectiveness and safety of CDT of alteplase and urokinase in the treatment of DVT in the lower extremities and the risk of bleeding are comparable, but alteplase achieved thrombolysis in a shorter time than urokinase. The above conclusions are limited by the quantity and quality of included studies and need to be verified by more high-quality research.